Technical note: Tips for drafting a mechanical patent - Muji Setiyo; Moehamad Aman; Hary Abdul Hakim (Community Empowerment, 2023)
Patents have an important role in increasing the competitiveness of a nation. Patents encourage researchers and inventors to develop new ideas, which allows them to obtain exclusive rights to their inventions. However, many researchers have produced outputs in the form of prototypes, processes, and key methods for making tools or products, but some of them have not registered legal protection for their findings in the form of patents because they are not competent to draft patent documents. Therefore, this technical note presents practical steps in preparing patent documents, especially for novice researchers. This technical note is limited to patents in the mechanical field. The examples provided are also only an alternative and not the only way to prepare patent documents. We hope that this technical note will benefit novice researchers and encourage them to register patents for their research findings.